Cost of a potential hydrogen-refueling network for heavy-duty vehicles with long-haul application in Germany 2050. (14th October 2021) - Nugroho, Rizqi; Rose, Philipp K.; Gnann, Till; Wei, Max
Abstract: Long-distance road-freight transport emits a large share of Germany's greenhouse gas (GHG) emissions. A potential solution for reducing GHG emissions in this sector is to use green hydrogen in fuel cell electric vehicles (FC-HDV) and establish an accompanying hydrogen refueling station (HRS) network. In this paper, we apply an existing refueling network design model to a HDV-HRS network for Germany until 2050 based on German traffic data for heavy-duty trucks and estimate its costs. Comparing different fuel supply scenarios (pipeline vs. on-site), The on-site scenario results show a network consisting of 137 stations at a cost of 8.38 billion € per year in 2050 (0.40 € per vehicle km), while the centralized scenario with the same amount of stations shows a cheaper cost with 7.25 billion euros per year (0.35 € per vehicle km). The hydrogen cost (LCOH) varies from 5.59 €/kg (pipeline) to 6.47 €/kg (on-site) in 2050. Highlights: Assessment of new refueling network design model and its cost for Germany in 2050. Results show a network consisting of 137 stations. Cost of an HDV-HRS network for on-site production is 8.38 bn€/a (6.47 €/kgH2 ). Cost of an HDV-HRS network for centralized production is 7.25 bn€/a (5.59 €/kg H2) . Centralized production needs H2 pipeline of 5381 km with 0.23 m average diameter.